TINJAUAN INFRASTRUKTUR PERDESAAN DALAM MENDUKUNG PRODUKTIVITAS PERTANIAN PERTANIAN DI DESA WATU KECAMATAN MARIORIWAWO KABUPATEN SOPPENG - Ameilia, Aulia; G, Henny Haerany; Siradjuddin, Irsyadi (Magister Administrasi Publik FISIP Universitas Mulawarman, 2024)
This research is a review of rural infrastructure in supporting agricultural productivity in Watu Village, Marioriwawo District, Soppeng Regency. The main problem in this research is how the availability of rural infrastructure affects agricultural productivity in Watu Village. This problem is viewed with a regional system approach and is discussed using the scoring analysis method and Chi Square analysis. The potential of the agricultural sector in Watu Village is quite large and the majority of the population make a living as farmers. The review of rural infrastructure in supporting agricultural productivity is one step to determine the extent of the influence of rural infrastructure in increasing agricultural productivity. The availability of adequate infrastructure is certainly able to support the increase in the area and existing agricultural products so that it can help improve the community's economy.